2017
DOI: 10.1007/s11356-017-8710-5
|View full text |Cite
|
Sign up to set email alerts
|

Financial feasibility of end-user designed rainwater harvesting and greywater reuse systems for high water use households

Abstract: Water availability pressures, competing end-uses and sewers at capacity are all drivers for change in urban water management. Rainwater harvesting (RWH) and greywater reuse (GWR) systems constitute alternatives to reduce drinking water usage and in the case of RWH, reduce roof runoff entering sewers. Despite the increasing popularity of installations in commercial buildings, RWH and GWR technologies at a household scale have proved less popular, across a range of global contexts. For systems designed from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 53 publications
7
26
0
3
Order By: Relevance
“…In a study from Spain, the perception of health risks from GWR showed a high influence on acceptability. Concerning the willingness to undertake operation and maintenance activities, 86% of participants were willing to perform these activities fortnightly, 69% twice a week, and 33% daily, coinciding with findings from previous studies [14].…”
Section: Formulation and Integrated Financial Assessment Of Alternatisupporting
confidence: 89%
See 4 more Smart Citations
“…In a study from Spain, the perception of health risks from GWR showed a high influence on acceptability. Concerning the willingness to undertake operation and maintenance activities, 86% of participants were willing to perform these activities fortnightly, 69% twice a week, and 33% daily, coinciding with findings from previous studies [14].…”
Section: Formulation and Integrated Financial Assessment Of Alternatisupporting
confidence: 89%
“…Although membrane filtration is more effective to achieve the required level of certain parameters, these systems have higher energy and The average water consumption was 130 + 61 litres per capita per day (lpcd) with a coefficient of variation (CV) of 47%. This consumption is similar to that reported in Colombia for stratum one households by Ángel, Rozo [26] (124 lpcd), and considerably lower than that reported by Oviedo-Ocaña, Dominguez [14] in stratum six households in the study area (203 lpcd). This value is also within the range of the indoor domestic water demand (excluding garden irrigation and other external uses) reported by Friedler and Hadari [9] and Londra, Theocharis [35] in developed countries.…”
Section: Formulation and Integrated Financial Assessment Of Alternatisupporting
confidence: 89%
See 3 more Smart Citations